Tadalafil as monotherapy and in combination regimens for the treatment of pulmonary arterial hypertension - Dioma U. Udeoji; Ernst R. Schwarz (Therapeutic Advances in Respiratory Disease, 2013)
The purpose of this review is to evaluate the use of tadalafil as monotherapy and in combination regimens for the treatment of pulmonary arterial hypertension (PAH). A systematic English language search of the medical literature using PubMed was conducted between January 1960 and May 2012 using the search terms ‘tadalafil’, ‘therapy’, ‘pulmonary (arterial) hypertension’ and ‘combination therapy’. Special emphasis was given to controlled clinical trials and case studies relevant for the use of tadalafil in PAH. The search revealed 113 relevant publications, 31 of which were clinical trials, 52 were reviews and 12 were case reports. Of these, 12 were clinical studies in human patients with PAH who were treated with tadalafil alone, and seven were clinical studies in human patients with PAH who were treated with tadalafil in combination with other agents. Only clinical studies in human patients were included. Exclusion criteria were monotherapy other than using tadalafil and any combination therapy that excluded tadalafil as part of the treatment regimen. Overall, 1353 human subjects were studied; 896 were treated with tadalafil alone while 457 subjects were treated with tadalafil in coadministration. Tadalafil appears to be an effective and a safe treatment option for patients with PAH. It improves clinical status, exercise capacity, hemodynamic parameters, compliance issues and quality of life and reduces the occurrence of clinical worsening. Tadalafil in combination therapy seems to be additive and synergistic in relaxing pulmonary vascular muscle cells but more clinical trials on human subjects are warranted.